THE IMPACT OF ACNE VULGARIS ON THE QUALITY OF LIFE IN TEEN PATIENTS - Damayanti -; Menul Ayu Umborowati; Zsa Zsa Ollyvia; Nining Febriyana (Jurnal Berkala Epidemiologi, 2022)
Background: Acne vulgaris (AV) is one of the most common cutaneous diseases in teenagers, which causes a decrease in self-esteem. Low self-esteem can affect the quality of life in AV patients. Purpose: This research aims to analyze the impact of AV on the quality of life in teenage patients based on their age, education level, and AV severity. Methods: This research used a non-probability purposive sampling technique and an observational analytic method with a cross-sectional design. The research location was SMPN 18 and SMAN 3 Surabaya. This study was conducted from August 2019 until January 2020. The samples were 109 teenagers; the total population was 2,121 teenagers. Research variables are AV severity and AV patients' quality of life. Research instruments were Lehmann’s Grading System for evaluating AV severity and Dermatology Life Quality Index (DLQI) in teenage AV patients. Data obtained was analyzed with the fisher-exact test method. Results: There were 46 (42.20%) males and 63 (57.80%) females in this study. DLQI results showed that AV had an enormous impact on quality of life in 12.80% of cases among all subjects. AV has a great potential to precipitate anxiety and affect the quality of life without considering the severity of the disease. Correlation between quality of life and age; quality of life and education level; quality of life and AV severity level resulted in p values of 0.19; 0.08; and 0.59. Conclusion: The management of AV in teenage patients should consist of individual treatment, education about AV, and its impact on the quality of life, as one of the critical social determinants of health.